The Effect of The Use of E-Learning Based on The Skype Application on Students' Learning Outcomes At YPSEI Vocational School, Palangka Raya Academic Year 2020/2021 - Agrapta, Kasepta; Toendan, Krisnayadi; Centauri, Beta (Universitas Lampung, 2021)
The use of electronic technology in learning provides reinforcement for the pattern of changing the learning paradigm. The E-Learning system is a form of learning implementation that utilizes technology and is not limited by space and time. Skype is one of the most popular applications and has the most users. In terms of user interface (User Interface) Skype is more attractive, and has complete features but still looks simple. The picture and sound quality is better, so most people prefer to use the Skype application compared to other applications. This study was conducted to determine the effect of using Skype application-based E-Learning on student learning outcomes at SMK YPSEI Palangka Raya for the academic year 2020/2021. This research is a descriptive research with a quantitative approach. The research sample is the students of SMK YPSEI Palangka Raya for the academic year 2020/2021 as many as 100 74 students. Data collection using questionnaires and documentation. While the data analysis technique using the Simple Regression test. The results showed that there was an effect of using Skype application-based E-Learning on student learning outcomes at SMK YPSEI Palangka Raya for the academic year 2020/2021 with the acquisition of a tcount of 14,744 and a significance value of 0.000 <0.05. So it can be concluded that the better the use of Skype application-based E-Learning, the higher the learning outcomes of students at SMK YPSEI Palangka Raya for the 2020/2021 school year. Keywords: Use of E-Learning, Skype Application, Learning OutcomesDOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202103